Designing capable and reliable products - Booker, J. D. (Butterworth Heinemann, 2001)
Designing Capable and Reliable Products offers an introduction to the importance of capability, quality and reliability in product development. It introduces the concept of capable design, focusing on producing designs that meet quality standards and also looks at linking component manufacture and its process capability with failure rates. It provides an introduction to reliable design, incorporating the probabilistic concept of reliability into the product design. This quantitative and highly practical volume provides practical methods for analysing mechanical designs with respect to their capability and reliability. Practising engineers who have to hit definite standards for design will find this book invaluable, as it outlines methods which use physically significant data to quanitify engineering risks at the design stage. By obtaining more realistic measures of design performance, failure costs can be reduced. Taking product design as its central theme, this book is a very useful tool for postgraduate students as well as professional engineers.
Keywords: Reliability (Engineering); Industrial design.; Manufacturing processes.; elektronické knihy; electronic books